The impact of a Framework‐aligned science professional development program on literacy and mathematics achievement of K‐3 students. Issue 9 (7th June 2017) - Paprzycki, Peter; Tuttle, Nicole; Czerniak, Charlene M.; Molitor, Scott; Kadervaek, Joan; Mendenhall, Robert
Abstract: This study investigates the effect of a Framework ‐aligned professional development program at the PreK‐3 level. The NSF funded program integrated science with literacy and mathematics learning and provided teacher professional development, along with materials and programming for parents to encourage science investigations and discourse around science in the home. This quasi‐experimental study used a three‐level hierarchical linear model to compare the Renaissance STAR Early Literacy, Reading, and Mathematics scores from 2015 to 2016 of K‐3 students in treatment and control classrooms in a large Midwestern urban school district. The statistically significant results indicate that, on average, every year that a student has a program teacher adds 8.6 points to a student's spring STAR Early Literacy score, 17.0 points to a student's STAR Mathematics score, and 41.4 points to a student's STAR Reading score compared to control students. Implications for early elementary teacher education and policy are discussed. © 2017 Wiley Periodicals, Inc. J Res Sci Teach 54:1174–1196, 2017